PELATIHAN JARINGAN KOMPUTER DAN MANAJEMEN INDUSTRI - Wowon Priatna (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
computer and Industrial Network Management Training is a non-profit program that improves the skills of trainees in computer network management and computer network development in the Industrial Revolution 4.0 era, with the aim of solving the problems faced by provincial and transmigration workers. Office Training Center. The most widely discussed problem is limited knowledge about computer networks and network implementation in the industrial world. The proposed solution is to offer participants support and training including: cabling engineering, TCP/IP concepts, device sharing, routing, Windows server installation and network management. The purpose of the training is to improve employee skills in mastering computer network languages. This is a mandatory skill that must be possessed by graduates of the Provincial Manpower and Transmigration Training Center. Training activities will be carried out for 2 (two) days, studying training programs and more interactive exercise-based learning. The results of this PKM show that online competency qualifications in the management of the education industry increased by 19.8%, an increase of 21.8%.